Dietary assessment and dietary guidelines across 11 European Union countries: a review from the PLAN’EAT project - Aureli, Vittoria; Grant, Federica; Aguilar-Martínez, Alicia; Brons, Anke; Fardet, Anthony; Chang, Betty; Vespa, Francesca; Kirschner, Jana; Kopczynska, Ewa; Böröcz, Lajos; Jacobsen, Maria; Ghukasyan, Siranush; et al. (Frontiers in Nutrition, 2026)
IntroductionThis paper presents a comparative assessment of dietary intake collection for surveillance and monitoring for adult population, Food Composition Databases (FCDBs), and Food-Based Dietary Guidelines (FBDGs) for children/adolescents, adults and the elderly population. Data and information were gathered until August 2025, concerning the 11 European countries participating in the European Horizon project PLAN’EAT “Food systems transformation toward healthy and sustainable dietary behavior.”MethodologyThis assessment was conducted through questionnaires completed by PLAN’EAT partners, who collected data from scientific literature and official documents in their native languages.ResultsDespite efforts such as the European Food Safety Agency’s EU Menu initiative to standardize dietary monitoring, significant inconsistencies persist in food intake assessment methodologies, database structures, and the development of dietary guidelines. These disparities hinder cross-country comparability, thereby limiting the evaluation of the effectiveness of EU-wide nutrition policies. The study identifies the aspects to be implemented in survey protocols, portion size assessment, software tools, and emphasizes the need to integrate current consumers’ eating habits when developing dietary guidelines. The importance of harmonizing data collection methods, ensuring regular national surveys, and synchronizing FBDGs updates with current consumption trends was emphasized. Key tools, such as adherence indicators and sustainability-integrated modeling approaches, were highlighted for their role in improving policy relevance and effectiveness. Diet modeling from countries like France, Germany, and the Netherlands were identified as best practices to be examined as scalable examples.DiscussionThis work emphasizes the need for more coordinated EU-level actions to promote methodological consistency, enhance the sustainability and inclusivity of FBDGs, and support the development of coherent, evidence-based nutrition policies. These efforts are essential to foster healthier diets and more sustainable food systems across Europe.